Cendawan dari Cairan Ecoenzyme dan Mama Enzyme Berbahan Organik Kulit Jeruk dan Kulit Rambutan - Harlin, Farah Ibtisamah; Handayani, Dezi (MASALIQ, 2024)
Ecoenzyme is a fermented mixture of organic waste, sugar and water in a ratio of 3:1:10. The results of fermentation can be liquid ecoenzyme, mama enzyme, and pitera. During the ecoenzyme fermentation process, microbes found in organic materials play a role in breaking down organic compounds to produce various useful metabolite compounds. The microbes found in ecoenzyme are generally Lactic Acid Bacteria (LAB) and fungi, but there is no literature that explains the types of fungi found in ecoenzyme liquid and mama enzyme from a mixture of several types of fruit peel. So it is necessary to isolate and identify the fungus from ecoenzyme and mama enzyme liquid with a mixture of orange peel and rambutan. This research is a descriptive study, with stages of equipment sterilization, making Potato Dextrose Agar (PDA) medium, making and taking ecoenzyme samples, isolating ecoenzyme samples, purifying fungi, macroscopic and microscopic observations, and identifying fungi. Data on the number of isolates and types of fungi isolated from ecoenzyme samples were analyzed descriptively and displayed in the form of tables and figures. The fungus that was successfully isolated from ecoenzyme and mama enzyme liquid with a mixture of orange peel and rambutan peel was 5 isolates. Two isolates belong to the mold group which refers to the genus Trichoderma and the genus Paecilomyces, three isolates belong to the yeast group, but have not been identified to the genus level.